Letter: tofacitinib use for biologic‐refractory paediatric inflammatory bowel disease. Issue 8 (7th October 2019) - Dolinger, Michael T.; Rolfes, Priya; Phan, Becky L.; Dubinsky, Marla C.
Abstract : LINKED CONTENT This article is linked to Ma et al paper. To view this article, visithttps://doi.org/10.1111/apt.15297 .